Penerapan Model Pembelajaran Pjbl Untuk Meningkatkan Keterampilan Dan Hasil Belajar Pada Mata Pelajaran IPAS Pada Siswa Kelas IV SD Negeri 2 Lumbungkerep Tahun Pelajaran 2022/2023 - KUSYANTI, KUSYANTI (Universitas Sebelas Maret, 2022)
This research was motivated by the low of student’ interesting in the IPAS subject. Beside that, a lot of students did not fulfil the KKTP in the evaluation test. Only 6 or 25% students fulfilled the KKTP. It was caused by the teacher centered in teaching learning process. The Project Based Learning (PjBL) could be used as an alternative learning model. It could invite the students more active and interactive in the classroom. So, the student interesting and the learning results were increase. The type of the research was the classroom actin research. It used Project Based Learning model. The object of the research was the forth-grade students of SDN 2 Lumbungkerep. The data was taken from observation, documentation and data collection. This research was conducted in 2 cycles. The first cycle was on 18-19 October 2022 and the second cycle was on 24 and 26 October 2022. Each cycle consisted of 4 stages, namely action planning, implementation, observation and reflection. And based on the student learning results, it increased from 13 to 22 students who fulfilled the KKTP. From this explanation, the application of PjBL model could increased the student interesting and the learning results in IPAS subject